A simple multi-responsive system based on aldehyde functionalized amino-boranes. Issue 7 (19th January 2018) - Shi, Yong-gang; Wang, Jun-wei; Li, Haijun; Hu, Guo-fei; Li, Xue; Mellerup, Soren K.; Wang, Nan; Peng, Tai; Wang, Suning
Abstract : An aldehyde functionalized amino-borane has been found to respond to multiple external stimuli such as temperature, pressure and solvents, producing distinct patterns and colours. Abstract : A simple aldehyde functionalized amino-triarylborane donor–acceptor system (BO-1 ) was found to display distinct responses toward multiple external stimuli including solvent, temperature and pressure, with emission colours changing from blue to red. The operating mechanism most likely involves reversible switching between closed and open structures based on an intramolecular B ← O bond. Imbedded donor–acceptor charge transfer transitions played a key role in the multi-coloured fluorescent response of this new boron system to external stimuli. Multi-coloured and erasable fluorescent images on solid substrates basedBO-1 's "turn-on" response toward solvents, particularly water, are demonstrated.